Dual‐direction high thermal conductivity polymer composites with outstanding electrical insulation and electromagnetic shielding performance. Issue 4 (5th January 2020) - Zhang, Yang; Tang, Bing; Liu, Yang; Feng, Rui; Song, Shaokun; Xiong, Chuanxi; Dong, Lijie
Abstract: The rapid dissipation of accumulated heat and efficient electromagnetic interference (EMI) shielding attract considerable attention due to the gradual integration and miniaturization of electronic devices. In an attempt to simultaneously overcome these issues, dual‐direction high thermal conductivity (TC) materials with outstanding electrical insulation and EMI shielding performance are urgently demanded. Herein, a tailor‐made sandwich network structure with insulated outer layer and EMI shielding middle layer is constructed by compression molding. The sandwich network structure endows the composite (#AB0.7/AM0.7/AB0.7) with high TC values of 3.051 and 3.365 Wm −1 K −1 at through‐plane and in‐plane directions, respectively, excellent electrical insulation (6.61 × 10 13  Ω cm, 3.25 kV/mm) and superior EMI shielding performance (>27.68 dB from 8.2 to 12.4 GHz). All these results demonstrate that the prepared composite with tailor‐made sandwich network structure is a promising candidate as ideal thermal management material for electronic devices.